2007
DOI: 10.1063/1.2434803
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of semiconductor laser dynamics under gigabit rate modulation

Abstract: A theoretical study of the dynamics of semiconductor lasers subjected to pseudorandom digital modulation at gigabit rates is presented. The eye diagram, turn-on jitter ͑TOJ͒, and power fluctuations in the modulated laser wave form are analyzed. The study is based on numerical large-signal analysis of the laser rate equations. Influences of the biasing and modulation currents on the eye diagram and TOJ are examined. The degree of eye opening is measured in terms of a Q factor of the laser signal analogous to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 28 publications
3
35
0
Order By: Relevance
“…This is because the relaxation oscillations in the 0 level are much enhanced near the threshold level, boosting the random effect of the bit pattern on the TOJ. 9,12 However, these oscillations are much damped with the increase in I b , which moderates the random effect of the bit pattern on TOJ in both 0 and 1 levels. To examine the influence of intrinsic noise on the explored results, we plot in the figure with dashed lines the corresponding variations in the TOJ when the intrinsic noise is ignored.…”
Section: A Toj and Eye Diagrammentioning
confidence: 99%
See 2 more Smart Citations
“…This is because the relaxation oscillations in the 0 level are much enhanced near the threshold level, boosting the random effect of the bit pattern on the TOJ. 9,12 However, these oscillations are much damped with the increase in I b , which moderates the random effect of the bit pattern on TOJ in both 0 and 1 levels. To examine the influence of intrinsic noise on the explored results, we plot in the figure with dashed lines the corresponding variations in the TOJ when the intrinsic noise is ignored.…”
Section: A Toj and Eye Diagrammentioning
confidence: 99%
“…10,11 Most recently, the authors showed that the bit-pattern induced TOJ is enhanced when the bit slot of a NRZ bit stream is shorter than the setting time of the relaxation oscillations. 12 When the semiconductor laser is biased near threshold, the TOJ is mainly a bit-pattern effect, whereas the intrinsic noise dominates at high bias levels. 12 lation current when the laser is biased above threshold.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 However, the physical process of large signal modulation (LSM) has rarely been investigated in the two-state lasing QD lasers yet so far, although it is directly related to fiber-optic communications. 16 In this letter, we theoretically investigate LSM response of two-state lasing in the InAs/GaAs QD lasers. GS lasing region (Region I), the transition region from GS lasing to two-state lasing (Region II) and the two-state lasing region (Region III) are compared and analyzed.…”
mentioning
confidence: 99%
“…The carriers also can escape back to the WL via those two ways. In addition, the current noise 16 and heating effect 19 are neglected for simplicity. Therefore, the rate equations can be written as follows:…”
mentioning
confidence: 99%